Strategic management of competitiveness trade enterprises in the post-war period - Polusmiak, Yuliia; Pavliuk, Tetiana; Baranov, Serhiy (Management and Entrepreneurship: Trends of Development, 2023)
The article is devoted to the improvement of the strategic management of the competitiveness of Silpo-Food LLC in the post-war period based on the analysis of its level of competitiveness through the development of a set of optimization measures. During the writing of the article, the theoretical and methodical bases of assessing the competitiveness of the enterprise were considered. On the basis of the theoretical material, the activity of Silpo-Food LLC was investigated, the economic activity of Silpo-Food LLC was analyzed, and directions for increasing the level of competitiveness of Silpo-Food LLC were proposed. The article analyzes the competitive environment of "Silpo-Food" LLC, during which it was determined that the instability of the economy, the decrease in the solvency of the population, the disruption of logistics chains, the loss of sales points due to significant destruction, the occupation of territories, attacks on the country's energy infrastructure, health hazards me and the lives of customers and employees - all these complications have a negative impact on the market to this day. Diagnostics of competitiveness management was carried out at Silpo-Food LLC. Based on the analysis, we note that the main components of managing the competitiveness of "Silpo-Food" LLC are: assortment policy; quality policy; work with suppliers; logistics system; HR; pricing policy; service policy; advertising activity. The following key principles for assessing the level of competitiveness of the enterprise were determined: complexity, systematicity, objectivity, dynamism, continuity and optimality. The main economic characteristics of the retail industry are analyzed. Porter's five forces model was used to analyze the attractiveness of grocery retail. Thus, the competition in domestic grocery retail can be characterized as intense. The paper analyzes strong and weak competitors by constructing maps of strategic groups. JEL Classification: D 21, M21